Practices of Teachers and Parents of Learners with Special Educational Needs During Pandemic - Rosales, Janna Marie L.; Ancheta Jr. , Rosein A.; Manalastas, Rebecca Dc.; De Los Reyes, Cecilia Elena P.; Etcuban, Jonathan O.; De Los Reyes, Niña Rozanne T.; Capuno, Reylan G.; Manguilimotan, Ramil P.; Pinili, Lilibeth C. (Future Science / FSH-PH Publications, 2022)
The research focused on the practices of teachers and parents of learners with special educational needs during pandemic employing descriptive-correlational research design. It specifically sought the demographic profile of the teachers and parent-respondents. Using purposive sampling, the respondents of the study consisted of 22 teachers and 26 parents from Academia De Santiago of Tarlac, and Angel Beats Play and Development Center, Manila, Philippines. The frequency count, percentage weighted mean, and correlation analysis were used to treat the data gathered from the survey-questionnaire. Results revealed that that the teacher-respondents “greatly encountered” behavioral problems and “encountered” cognitive development problems in handling LSENs; parent-respondents “encountered” both behavioral and cognitive development problems. There was a “great extent” of practices of teachers while “little extent” in parents’ practices. There was a significant relationship between the demographic profile of the teacher-respondents and the extent of teachers’ practices. Based from the significant findings drawn, this study recommends to upskill teachers’ competencies in handling learners with special education needs. Finally, implementation of the action plan is hereby recommended to improve the behavioral and cognitive aspects of the learners and to further improve practices of teachers and parents of the home-schooled learners with special educational needs during a pandemic and its aftermath.